The Power of the Periphery - Anker, Peder (Cambridge University Press, 2022)
What is the source of Norway's culture of environmental harmony in our troubled world? Exploring the role of Norwegian scholar-activists of the late twentieth century, Anker shows how their portrayal of Norway as a pristine natural environment of the periphery led to it being fashioned as an idealised ecological microcosm. This title is also available as Open Access on Cambridge Core.